Artificial Intelligence (AI) Chatbot in EFL Writing: Exploring Students’ Perspectives - Janah, Rohmatul; Tusino, Tusino; Dewi, Puspa (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2025)
This study aims to investigate students‘ perceptions of the usefulness of AI Chatbot (ChatGPT) in improving writing skills and identifying perceived weaknesses in writing classes. The study employed a qualitative case study method at Muhammadiyah University of Purworejo, using questionnaires and interviews with fourth-semester English education students in the 2024/2025 academic year. The results revealed that students generally had positive perceptions of AI Chatbots in enhancing their writing skills, especially in idea generation, structure organization, and confidence building. Questionnaire data showed high agreement percentages and mean scores, particularly on statements about the value of AI in expressing ideas and improving writing skills. However, interviews uncovered challenges such as generic and shallow responses, inaccurate or fabricated references, over-reliance that reduces critical thinking, informal language styles, and misinterpretation of prompts. These findings highlight both the benefits and limitations of AI Chatbots in academic writing and underline the need for critical AI literacy and human guidance in educational contexts.